Evaluación de las estrategias de comunicación que utiliza el CONSEP para apoyar el sistema de tratamiento, rehabilitación y reinserción social de las personas consumidoras y dependientes de las sustancias psicoactivas. - Granja Ballesteros, Andrea Belén (2013)
This theoretical work covers important topics on the subject of drugs, the social communication and society in general. All linked, and that are impacted by the different uses that each receives. This research paper consists of three chapters than contain essential information to understand the issues raised. In brief the reader is invited to delve into the areas to the first chapter, where it has covered the topic of communication and health, revealing the principal concepts of each term and its importance in the life of human beings. Especially the importance to use the tools of the massive media to promote prevention and improve the health and lifestyle of the citizenry